2002
DOI: 10.1074/jbc.m206861200
|View full text |Cite
|
Sign up to set email alerts
|

A Physical and Functional Interaction between Yeast Pol4 and Dnl4-Lif1 Links DNA Synthesis and Ligation in Nonhomologous End Joining

Abstract: Genetic studies have implicated the Saccharomyces cerevisiae POL4 gene product in the repair of DNA double-strand breaks by nonhomologous end joining. Here we show that Pol4 preferentially catalyzes DNA synthesis on small gaps formed by the alignment of linear duplex DNA molecules with complementary ends, a DNA substrate specificity that is compatible with its predicted role in the repair of DNA double-strand breaks. Pol4 also interacts directly with the Dnl4 subunit of the Dnl4-Lif1 complex via its N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 55 publications
(62 reference statements)
6
112
0
1
Order By: Relevance
“…2 The present study suggests that Pol , with its unusually high rate for misalignment-mediated errors and its preference for short gap substrates, also appears to be well suited to participate in NHEJ. The possible involvement of Pol in this process is further suggested by genetic (50) and biochemical studies (51) indicating that in yeast, end-joining depends upon the function of DNA Pol IV, a close homologue of human Pol . In a recent study, Heidenreich et al (52) showed that NHEJ contributes to mutagenesis in non-replicating diploid yeast cells.…”
Section: Fidelity Of Dna Polymerasementioning
confidence: 99%
See 1 more Smart Citation
“…2 The present study suggests that Pol , with its unusually high rate for misalignment-mediated errors and its preference for short gap substrates, also appears to be well suited to participate in NHEJ. The possible involvement of Pol in this process is further suggested by genetic (50) and biochemical studies (51) indicating that in yeast, end-joining depends upon the function of DNA Pol IV, a close homologue of human Pol . In a recent study, Heidenreich et al (52) showed that NHEJ contributes to mutagenesis in non-replicating diploid yeast cells.…”
Section: Fidelity Of Dna Polymerasementioning
confidence: 99%
“…This specificity is characteristic of Pol and thus suggests the involvement of Pol IV. The end-joining activity of Pol IV requires the presence of its N-terminal BRCT domain (50,51). It has been shown that through the BRCT domain, Pol IV interacts with Dnl4, a subunit of the Dnl4-Lif1 complex (51), which is the homologue of the human ligase IV-XRCC4 complex.…”
Section: Fidelity Of Dna Polymerasementioning
confidence: 99%
“…A third domain, the breast cancer carboxy-terminal (BRCT)-associated domain is also found in many family X members, including the single Pol X members in S. cerevisiae [Tseng and Tomkinson, 2002] and Schizosaccharomyces pombe [Gonzalez-Barrera et al, 2005] and three out of the four Pol X members (not Pol b) in vertebrates [Aoufouchi et al, 2000]. Pol X members have a single BRCT domain, unlike many BRCT domain-containing proteins (including ligase IV) where the domains are present as one or more tandemly repeated pairs [Leung and Glover, 2011].…”
Section: Breast Cancer Carboxy-terminal Domainmentioning
confidence: 99%
“…As with other BRCT domains, the BRCT domain in TdT can also interact with a phosphoserine-containing motif, but whether this has functional relevance is not yet clear [Yu et al, 2003]. Rather, in all examples tested (Pol4 [Tseng and Tomkinson, 2002] as well as vertebrate Pol k [Fan and Wu, 2004;Lee et al, 2004;Ma et al, 2004;Nick McElhinny et al, 2005;Mueller et al, 2008], Pol l [Mahajan et al, 2002;Ma et al, 2004;Nick McElhinny et al, 2005;DeRose et al, 2007] and TdT), the BRCT domain is required for physical interaction with Ku and XRCC4-ligase IV at DNA ends, and there is as yet Environmental and Molecular Mutagenesis. DOI 10.1002/em no contribution of Ku, XRCC4, or ligase IV phosphorylation.…”
Section: Breast Cancer Carboxy-terminal Domainmentioning
confidence: 99%
See 1 more Smart Citation